Esophageal intramural hematoma: An unusual cause of acute onset chest pain (Indian Journal of Case Reports, 2025)
An elderly lady in her mid-70 s who is known to have coronary artery disease for which she was on dual antiplatelet therapy, presented with acute onset chest pain and dysphagia. The cardiac evaluation was unremarkable. Esophagogastroduodenoscopy (EGD) showed a large intramural hematoma in the esophagus, causing luminal narrowing. A diagnosis of esophageal intramural hematoma secondary to antiplatelets was made based on the findings of Gastrografin swallow, EGD, and contrast-enhanced computed tomography of the thorax along with the history of taking dual antiplatelets. Antiplatelets were subsequently stopped. She was managed in the critical care unit with intravenous fluids, pantoprazole infusion, empirical antibiotics, fentanyl infusion, and total parenteral nutrition. The relook EGD showed a resolving hematoma. She was maintained on intravenous pantoprazole, allowed to take oral feeds gradually, and was subsequently discharged. To conclude, intramural hematoma of the esophagus can present with acute chest pain and dysphagia. Careful history taking, especially the drug history and appropriate investigations, are pivotal as there are high chances of misdiagnosis and unwanted anticoagulant therapy.